An ionic liquid as an interface modulator for highly efficient and stable perovskite solar cells. Issue 8 (29th March 2023) - Chen, Xiang; Song, Lixin; Gu, Ningxia; Zhang, Pengyun; Ning, Lei; Du, Pingfan; Chen, Fengfeng; Xiong, Jie
Abstract : In this paper, an ionic liquid (BMIMHSO4 ) was used to regulate the TiO2 /perovskite interface. The interfacial interaction makes the BMIMHSO4 a connection in TiO2 and perovskite layers, providing high-efficiency electron extraction and thus improving device performance. Abstract : Perovskite solar cells (PSCs) are emerging technologies that have been heavily researched due to their outstanding photoelectric properties. However, the majority of recombination losses occur at the interface between perovskite and the ETL, resulting in their full potential not yet being reached. In this work, ionic liquid (IL) 1-buty-3-methylimidazole hydrogensulfate (BMIMHSO4 ) was employed to regulate the TiO2 /perovskite interface. BMIMHSO4 formed a surface dipole, which realigned the TiO2 conduction band upward, allowing for faster charge extraction, and lower energy loss at the interface. Furthermore, the BMIMHSO4 induced a vertical crystal arrangement, decreased the perovskite defect density, and reduced the defect-induced charge recombination in MAPbI3 -based PSCs. Consequently, the power conversion efficiency (PCE) was improved from 15.92% to 19.13%. Moreover, the un-encapsulated device exhibited improved stability and retained 90% of its original value after 600 storage hours. This work demonstrated a practical technique to optimize the interface by applying an IL, thus achieving high-performance PSCs.